Parents' Perception of Inclusive Education For Children With Special Needs - Sitanggang, Benni; Tarigan, Della Betsya; Astuti, Chiva Indri; Ringo, Anggun Daniela; Ramayani, Juli; Fajriana, Retno Rezky (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2025)
his study aims to analyze parents' perceptions of inclusive education for children with special needs (CSN) and the factors influencing their decision to choose inclusive schools. Employing a qualitative approach with a descriptive method, data were collected through semi-structured interviews with parents of CSN in Pancur Batu District. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques to identify key emerging patterns. The findings indicate that parents' perceptions of inclusive education vary. Some parents support inclusive education due to its benefits in enhancing children's social interactions and independence. However, others express concerns regarding school readiness, the limited availability of trained educators, and the social stigma surrounding CSN. Economic factors and personal experiences also play a role in parents' decision-making when selecting a school for their children. Therefore, comprehensive policies are needed to support inclusive education, including enhanced training for educators, improved facilities, and broader public awareness campaigns. Strengthening collaboration among the government, schools, and communities is also essential to creating a more inclusive learning environment that optimally supports the development of CSN.